Effect of expression of immunohistochemical marker Ki-67 on the life expectancy of patients with gastric cancer 0-III stages - O. M. Levyk; A. I. Shevchenko; V. A. Tumanskiy; A. V. Evseyev (Zaporozhye State Medical University, 2015)
In Ukraine 60,9% of patients with gastric cancer die within 1 year after ascertainment of diagnosis. Aim: In order to investigate the effect of Ki-67 overexpression on life expectancy, study was conducted among 129 patients with gastric cancer of 0 - III stages, who received treatment in Zaporizhzhia Regional Clinical Oncology Center from June 2006 till October 2013. Methods and results. All patients included in the study underwent radical surgical treatment. 62 patients with gastric cancer (48%) received adjuvant chemotherapy. Immunohistochemical study was performed using monoclonal antibodies Mo a-Hu Ki-67 Antigen, Clone MIB-1. It has been found that the Ki-67 overexpression is observed in 65,9% of the tumor tissue of gastric cancer patients and indicates aggressive process. Conclusion. Using adjuvant chemotherapy among patients with gastric cancer II stage significantly improves the life expectancy (p <0.05) in cases when patients have the presence of high Ki-67 proliferative activity.